Implementasi Qawā`id Fiqhiyyah dalam Ekonomi Syariah - Awal Rifai (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2022)
This study aims to determine the implementation of qawā`id fiqhiyyah in Islamic economics. This research is library research with qualitative method. The approach used in this study is a descriptive normative approach. The results of the study show that the role of fiqh rules in legal practice in general and in sharia economic issues in particular is very clear as contemporary problems appear that seem endless. The existence of fiqh rules in sharia economics is actually very helpful in concluding the law of a problem. Almost all of the fiqh rules that have been formulated by the scholars can be implemented in sharia economic problems.